Coverage control for mobile sensor networks subject to bounded measurement errors - Song, Cheng; Fan, Yuan (Chinese Control Conference, 2020)
The coverage control problem for mobile sensor networks with bound position measurement errors on a circle is addressed in this paper. A practical measurement error model is considered in which only the upper bound on each sensor's measurement error is assumed to be known by it a priori. Firstly, the upper bound on the measurement errors are employed to design an estimation algorithm for each sensor to estimate the difference between neighboring sensors' positions. Then, a distributed coverage control law is developed by using the estimated difference to drive networked mobile sensors to a neighborhood of the optimal configuration. It is shown that the effect of the measurement errors on the coverage performance can be reduced or even eliminated under the proposed coverage control law.